2017
DOI: 10.1080/17482631.2017.1356674
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the early chain of healthcare: lifeworld hermeneutics from the patient’s perspective

Abstract: Purpose: Patients must be able to feel as much trust for caregivers and the healthcare system at the healthcare centre as at the emergency department. The aim of this study is to explain and understand the phenomenon of trust in the early chain of healthcare, when a patient has called an ambulance for a non-urgent condition and been referred to the healthcare centre.Method: A lifeworld hermeneutic approach from the perspective of caring science was used. Ten patients participated: seven female and three male. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…A deeper description of experiences of the decision support through the specific collaboration however lacks. Other studies found a similar result of dialogue being important to establish trust (Norberg Boysen et al, 2017 ), and that patients cared for in PHC centres and EDs when calling for an ambulance have similar trust in the received care (Norberg Boysen et al, 2019 ). There is always an understanding gap in the dialogue due to encounters consisting of persons with different lifeworlds, meaning that previous experiences and knowledge affect the understanding of the situation (Dahlberg et al, 2008 ).…”
Section: Discussionmentioning
confidence: 72%
“…A deeper description of experiences of the decision support through the specific collaboration however lacks. Other studies found a similar result of dialogue being important to establish trust (Norberg Boysen et al, 2017 ), and that patients cared for in PHC centres and EDs when calling for an ambulance have similar trust in the received care (Norberg Boysen et al, 2019 ). There is always an understanding gap in the dialogue due to encounters consisting of persons with different lifeworlds, meaning that previous experiences and knowledge affect the understanding of the situation (Dahlberg et al, 2008 ).…”
Section: Discussionmentioning
confidence: 72%
“…Contact between healthcare professionals, the patient, and the caregivers must be based upon understanding and trust [ 34 ]. To achieve this, it is essential that HCPs have knowledge and competence in the field, can provide timely and necessary information, and acknowledge and support the caregivers in their tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Norberg and colleagues described this chain of trust and healthcare delivery spanning from the moment that a patient calls an ambulance to the various healthcare transitions in the patient's journey. [26,27] Trust matters in healthcare. Calnan & Rowe suggest that when competence and experience characterize healthcare, the patient believes health professionals will provide adequate treatment and make them feel secure.…”
Section: Discussionmentioning
confidence: 99%